Schooling: Crossing Cultural Borders - Herbert, Susan (Daily Express, 2002)
This article explores the ways in which culture can impact on schooling, and suggests that in order to facilitate successful cultural border crossing by students, teachers in Trinidad and Tobago need to become truly accommmodating of diversity, with respect to the students in their charge
Keywords: Inclusive education; Cultural factors; Educational environment; Trinidad and Tobago